Building Safer Healthcare Systems A Proactive, Risk Based Approach to Improving Patient Safety - Spurgeon, Peter; Sujan, Mark-Alexander.; Cross, Stephen; Flanagan, Hugh.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a new, practical approach to healthcare reform. Departing from the priorities applied in traditional approaches, it instead assesses - both theoretically and practically - the successful lessons learned in other safety-critical industries, and applies them to healthcare settings. The authors focus on the importance of human factors and performance measures to establish proactive, systematic methods for healthcare system design. This approach helps to identify potential hazards before accidents occur, enhancing patient safety. In addition, the book details the new approach on the basis of real-world applications in the NHS and insights from NHS staff. Case studies and results are presented, demonstrating the significant improvements that can be achieved in risk reduction and safety culture. Lastly, the book outlines what steps healthcare organisations need to take in order to successfully adopt this new approach. The approach and experiential learning is brought together through the development of a new holistic patient safety education syllabus.
Introduction -- The Continuing Issues of Patient Safety: Data on the Nature and Persistence of Harm, Limitation of Current Approaches -- Proactive Search for Risk: Lessons From Other Safety Critical Industries -- Human Factors - Human Error and Beyond, Performance Influencing Factors, Systems Thinking, High Reliability Organisations -- Patient Safety Culture - Measurement and Implications -- The Safer Clinical Systems Programme -- The 5 steps of the Safer Clinical Systems approach -- Improving the Safety of Handover and Communication -- Next steps towards a proactive, risk based approach to improving patient safety in the health sector. .
Keywords: Security systems; Public health administration; Practice of medicine; Hospitals -- Administration; Biomedical engineering; Security Science and Technology; Health Administration; Practice and Hospital Management; Biomedical Engineering and Bioengineering